Cognitive impairment profile in adult patients with Niemann pick type C disease - Camille Heitz; Stéphane Epelbaum; Yann Nadjar (Orphanet Journal of Rare Diseases, 2017)
Abstract Background Cognitive impairment is one of the core symptoms of Niemann Pick type C (NPC) disease, but few data concerning the neuropsychological profile of NPC patients are available. The aim of our study was to characterize cognitive impairments in NPC disease and to assess the evolution of these symptoms and the impact of miglustat on cognitive follow-up. Methods We conducted a retrospective study of 21 adult patients diagnosed with NPC disease. Neuropsychological data (global cognitive efficiency, language, attention, executive functions, praxis, and visuoconstructive functions tests) were retrieved to describe the cognitive profile of patients. Cognitive impairment scores over time were assessed under treatment by miglustat. Results The majority of patients (90%) were impaired in one or more cognitive function. Executive functions and attention were the most impaired cognitive functions. Conversely, storage in the episodic memory was preserved in 61.5% of cases. Mean neuropsychological scores were stable during the period under miglustat (mean of 3.8 years). Conclusions This study is one of the first to assess the cognitive profile of adult NPC patients. This profile is not specific to attention and executive dysfunctions; however, the preservation of storage in the episodic memory is promising for cognitive remediation. Further studies are needed to confirm the role of miglustat on cognition, but in this study, patients were stable under this treatment.